The Influence of Q.S. Al-Hadid 20 on Parenting and Muslimah Character Formation in Islamic Boarding Schools - Nazilah, Ilma Ainun; Kahar, Abd. (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2025)
The main character education for a child is the family environment. This article describes the parenting pattern and strengthening of modern Muslimah character with the values of the Al-Quran Surah Al-Hadid verse 20 at the Al-Mujtama' Al-Islami Islamic Boarding School in Pamekasan Regency, Madura. This research uses a qualitative approach with a phenomenological approach. Data sources were taken from six informants consisting of 3 teachers and 3 administrators. With data collection techniques of interviews, observation, and documentation. Stages of data condensation, data display, and conclusion drawing. The results of the study concluded that the typology of parenting patterns applied tends to be democratic parenting patterns. The values of the Muslimah character based on research findings inspired by the Al-Hadid verse 20 of the Qur'an include obedience, compassion, discipline, sincerity, and caring for the environment.